CceR and AkgR Regulate Central Carbon and Energy Metabolism in Alphaproteobacteria - Saheed Imam (American Society for Microbiology, 2015)
ABSTRACT  Many pathways of carbon and energy metabolism are conserved across the phylogeny, but the networks that regulate their expression or activity often vary considerably among organisms. In this work, we show that two previously uncharacterized transcription factors (TFs) are direct regulators of genes encoding enzymes of central carbon and energy metabolism in the alphaproteobacterium Rhodobacter sphaeroides. The LacI family member CceR (RSP_1663) directly represses genes encoding enzymes in the Entner-Doudoroff pathway, while activating those encoding the F1F0 ATPase and enzymes of the tricarboxylic acid (TCA) cycle and gluconeogenesis, providing a direct transcriptional network connection between carbon and energy metabolism. We identified bases that are important for CceR DNA binding and showed that DNA binding by this TF is inhibited by 6-phosphogluconate. We also showed that the GntR family TF AkgR (RSP_0981) directly activates genes encoding several TCA cycle enzymes, and we identified conditions where its activity is increased. The properties of single and double ΔCceR and ΔAkgR mutants illustrate that these 2 TFs cooperatively regulate carbon and energy metabolism. Comparative genomic analysis indicates that CceR and AkgR orthologs are found in other alphaproteobacteria, where they are predicted to have a conserved function in regulating central carbon metabolism. Our characterization of CceR and AkgR has provided important new insight into the networks that control central carbon and energy metabolism in alphaproteobacteria that can be exploited to modify or engineer new traits in these widespread and versatile bacteria. IMPORTANCE To extract and conserve energy from nutrients, cells coordinate a set of metabolic pathways into integrated networks. Many pathways that conserve energy or interconvert metabolites are conserved across cells, but the networks regulating these processes are often highly variable. In this study, we characterize two previously unknown transcriptional regulators of carbon and energy metabolism that are conserved in alphaproteobacteria, a group of abundant, environmentally and biotechnologically important organisms. We identify the genes they regulate, the DNA sequences they recognize, the metabolite that controls the activity of one of the regulators, and conditions where they are required for growth. We provide important new insight into conserved cellular networks that can also be used to improve a variety of hosts for converting feedstock into valuable products.